Alcohol-induced blackouts and maternal family history of problematic alcohol use. (June 2015) - Marino, Elise N.; Fromme, Kim
Abstract: Background: Consequences of heavy drinking include alcohol-induced blackouts, which are periods of amnesia for all or part of a drinking event. One risk factor for blackouts is family history of problematic alcohol use (FH +); however, research rarely distinguishes maternal from paternal FH +. The objective of this study was to examine whether maternal or paternal FH + better predicts likelihood of experiencing blackouts than a general measure of overall FH +, and whether gender moderates this association. Method: Participants (N = 1164; 65.4% are female) were first-time college freshmen (age range = 17–19) who participated in a 6-year, 10-assessment, longitudinal study in the United States. Alcohol-induced blackouts, the dependent measure, were dichotomized (yes/no) based on endorsement of memory problems after drinking using a single item during Years 4–6. FH +, captured at baseline, was coded if participants self-reported that their mother, father, or any of their four grandparents were a possible or definite problem drinker. Results: Overall, 773 (66.4%) participants reported experiencing blackouts during Years 4–6. Women were more likely to report blackouts than men; however, compared with women with a maternal FH +, men with a maternal FH + were more than twice as likely to report blackouts. Discussion: Men appear to be more susceptible than women to the effects of a maternal FH +. Genetic and environmental explanations for this finding are discussed. In sum, these findings are an important step toward understanding a significant yet understudied negative consequence of heavy alcohol use. Highlights: 66.4% of university students reported blackouts. Controlling for drinking, women had a greater likelihood of experiencing blackouts. Men with a maternal family history of alcohol problems were more likely to black out.